Sturge-Weber Syndrome (Sws) With Occipital Epilepsy: Two Cases Presented In A Tertiary Care Hospital - Mahmud, Reaz (Journal of Dhaka Medical College, 2023)
Sturge-Weber syndrome is a rare sporadic, neurocutaneous syndrome. In most instances, the patients present with seizures other than the port-wine stain and ipsilateral leptomeningeal angiomata. The documentation of seizures’ semiology in the current literature is scarce. Here we reported two cases who presented with visual hallucination as an ictal phenomenon and associated ictal headache and vomiting. The phenomenology was very close to migraine with aura. A careful history, associated seizure, and EEG findings helped in differentiation. Both the cases responded well with carbamazepine. J Dhaka Med Coll. 2021; 29(1): 118-222